'[T]o Make us Complete as Human Beings': Soil as the Bedrock of Collected Memories in Niq Mhlongo's Paradise in Gaza. Issue 1 (2nd January 2023) - Bosman, Sean James
Abstract: Niq Mhlongo's Paradise in Gaza (2020) uses images related to soil to emphasize the novel's concern with the transmission of indigenous knowledge and the relationship between a sense of humanity and land ownership. Mhlongo's novel not only explores the quotidian and practical relationship between its characters and the land they occupy and cultivate, but also suggests a transcendental and spiritual relationship between them. With reference to work by Maurice Halbwachs, James E. Young, and Viet Thanh Nguyen, I argue that Mhlongo's inscription of soil reflects an authorial concern with the entanglements amongst collected memories, just memories, the transmission of culture, land ownership and human dignity. I present a close reading of key passages from the novel using Sarah Nuttall's notion of entanglement to demonstrate these relationships. Ultimately, I argue that Paradise in Gaza is not only an exploration of African life in a historical setting, but that it also presents an argument for the need for some form of land restitution in contemporary South Africa while recognizing the complexities inherent in any such process.